Negrosul: Centro de Tradições Gaúchas na contramão do racismo: espaços de afirmação, resistência e patrimônio do povo negro - Santos, Isadora Bispo dos (2022)
The research presents the perspectives for recognition of the Centro Tradicionalistas Gaúchos Negros within the scope of the Traditionalist Gaúcho MTG Movement and in the society of the State of Rio Grande do Sul in view of the cultural and social role that these entities developed during their trajectories. The guiding problem of this work concerns the investigation of the relevance of rescue actions, valorization and recognition of the participation of the black subject in the formation of the State and the struggle of these insurgent spaces against racism and segregation. The study is dedicated to the cases of CTGs Ronda Crioula in the municipality of São Sepé and CTG Clareira da Mata in the municipality of Caçapava do Sul, both founded during the 70s. Therefore, the objective of this research is to reconstruct the trajectory of CTGs Negros Ronda Crioula and Clareira da Mata, traditionalist entities, as spaces of the cultural heritage of Rio Grande do Sul, in addition to bringing the specifics of these two centers. The methodological bias will be that of oral history, as it is a method that is related to orality, an important factor that transmits culture and information for generations in Black and African Cosmology.